Innovation in The Application of The State Personnel Notification System (Sinoken) In Regional Office IX, Jayapura State Personnel Agency - Muh Fatlullah Baqi Bando; Badu Ahmad; Syahribulan Syahribulan (Institute of Computer Science (IOCS), 2023)
In the age of Industry 4.0 and digital transformation, the government constantly innovates in implementing e-government. The use of the Civil Service Notification Information System (SINOKEN) application is an example of e-government-based public service implementation. The goal of this study was to analyze and describe the innovative results of the application of the Civil Service Notification Information System (SINOKEN) at Regional Office IX of the Jayapura State Civil Service Agency using Rogers' five characteristics of innovation, which are relative advantage, compatibility, complexity, trialability (ability to experiment), and observability (can be observed). This study employed a qualitative research method to describe what happens in the field, which will later facilitate objective and precise data related to the problem. Heads of Transfers and Employment Status, Section Heads/Coordinators for Transfers and Employment Status, Computer Staff, Employees who run the SINOKEN application, and Agencies or users of the SINOKEN application service were among the informants in this study (who represent). The study's findings showed that staffing services using the innovative SINOKEN application are measured by the five characteristics of Roger's innovation that have been well implemented and received positive responses from various vertical agencies or districts/cities in the Papua Province region. Consequently, it is still difficult to access a stable internet network in some areas and there is still a lack of resources, the SINOKEN application is gradually being used in several staffing services at Regional Office IX of the Jayapura State Civil Service Agency, especially in the Field of Mutations and Employment Status. In the Papua Province region, adequate human resources are needed in district/city regional agencies.